PENGEMBANGAN E-MODUL BERBANTUAN APLIKASI CALIBRE YANG BERBASIS AUGMENTED REALITY (AR) PADA MATERI SIKLUS AKUNTANSI PERUSAHAAN DAGANG KELAS X AKUNTANSI SMK NEGERI DI SURABAYA - Cindy Eva Dufana; Susanti Susanti (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2025)
This research aims to produce e-module teaching materials assisted by the Caliber application based on Augmented Reality (AR) on trading company accounting cycle material. Therefore, an e-module assisted by the Caliber application based on Augmented Reality (AR) was developed to support the implementation of the independent curriculum in vocational schools. This development research (R&D) uses the ADDIE development model. The e-module that is developed is first reviewed and validated by experts. Then it was applied to 32 students in class X Accounting at State Vocational Schools in Surabaya. The research results showed that the validation results for material experts were 90.75%, language experts were 88%, media experts were 93%, and student responses were 99.69% with the e-module category being very suitable for use as teaching material in the learning process.